China's Trump card: cryptocurrency and its game-changing role in Sino-US trade - Yeung, Raymond Y. T. (Hoboken: Wiley, 2020)
'The trade war and geopolitical issues have increased the risk of a financial decoupling between China and the US, the world's two largest economies. This book provides a thorough analysis of the major issues underlying the economic conflict and presents new factors coming into play as the global economy undergoes digital transformation As the trade war between the US and China escalates, with the US continuing to raise new tariffs on Chinese goods and China hitting back in kind, there seems to be no end in sight to the economic battle. The World Economy in Digital Times provides an in-depth discussion on this import tit-for-tat battle and sheds light on the various underlying issues whose scope is beyond the normal trade negotiations. On the surface, the economic dispute seems to have been brought about by globalization and protectionism. However, Raymond Yeung argues that the deeper reason behind this is the currency misalignment and the current global trade arrangement'--
Includes bibliographical references and index.
Keywords: China -- Commerce -- United States; United States -- Commerce -- China; Tariff -- China; Tariff -- United States; China -- Foreign economic relations -- United States; United States -- Foreign economic relations -- China; Trump,Donald, -- 1946-